2013
DOI: 10.1007/s00792-013-0550-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for surfactant production by the haloarchaeon Haloferax sp. MSNC14 in hydrocarbon-containing media

Abstract: The potential for surfactant production by the extreme halophilic archaeon Haloferax sp. MSNC14 in the presence of individual hydrocarbon substrates was studied. This strain was selected for its ability to grow on different types of hydrocarbons at high NaCl concentrations. Linear (n-heptadecane or C17) and isoprenoid (pristane) alkanes, a polyaromatic hydrocarbon (phenanthrene) and ammonium acetate (highly water-soluble control compound) were used as growth substrates. The adherence potential was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Strains from the Persian Gulf coast capable of both hydrocarbon utilization and volatilization of toxic mercury were recently reported [47]. A Haloferax strain was found to produce surfactants that enhanced hydrocarbon degradation [48]. Additionally, an Arhodomonas strain was reported to have the capability to degrade aromatic compounds, including benzene and toluene [49].…”
Section: Halophilic Transformations For Biotechnologymentioning
confidence: 99%
“…Strains from the Persian Gulf coast capable of both hydrocarbon utilization and volatilization of toxic mercury were recently reported [47]. A Haloferax strain was found to produce surfactants that enhanced hydrocarbon degradation [48]. Additionally, an Arhodomonas strain was reported to have the capability to degrade aromatic compounds, including benzene and toluene [49].…”
Section: Halophilic Transformations For Biotechnologymentioning
confidence: 99%
“…Haloferax st. MSNC 14 also grew on phenanthrene while the other three isolates could not [ 18 ]. Later research found that Haloferax st. MSNC 14 produced surfactants during growth on n -heptadecane, pristane, and phenanthrene, but not during growth on acetate [ 31 ]. Thus, it was able to increase the bioavailability of low-solubility hydrocarbons during their degradation [ 31 ].…”
Section: Archaea In the Degradation Of Organicsmentioning
confidence: 99%
“…Later research found that Haloferax st. MSNC 14 produced surfactants during growth on n -heptadecane, pristane, and phenanthrene, but not during growth on acetate [ 31 ]. Thus, it was able to increase the bioavailability of low-solubility hydrocarbons during their degradation [ 31 ]. Four strains were also isolated from soil and water in a hypersaline coastal area of the Arabian Gulf ( Haloferax st. HA-1, Haloferax st. HA-2, Halobacterium st. HA-3, and Halococcus st. HA-4) with a multitude of alkane and aromatic degradation abilities [ 16 ].…”
Section: Archaea In the Degradation Of Organicsmentioning
confidence: 99%
“…The degradation of unsaturated and saturated alkanes by different types of sulfatereducing microorganisms (Grossi et al 2011;Hakil et al 2014), including a hyperthermophilic archaeon widespread in petroleum reservoirs (Khelifi et al 2010a(Khelifi et al , b, 2014, has been documented. The diversity of hydrocarbonoclastic microorganisms adapted to high salinity (Tapilatu et al 2010a) or high hydrostatic pressure (Tapilatu et al 2010b) and some original strategies to use hydrocarbons under such harsh environmental conditions (Grossi et al 2010;Silva et al 2010;Djeridi et al 2013) were also highlighted. Clearly, the capacity of extremophiles to grow on hydrocarbons still remains underestimated and undoubtedly deserves further attention for many ecological, geochemical, environmental, and biotechnological reasons.…”
Section: Pollutants and Microbesmentioning
confidence: 99%